Empowering Women Entrepreneurs through Legal Reform and Business Associations - Nadgrodkiewicz, Anna; Siddiqui, Hammad (World Bank, Washington, DC, 2012)
In 2010, Pakistan ranked 133 out of the 134 countries evaluated by the World Economic Forum's Global Gender Gap Report on economic participation and opportunity for women, lower than Saudi Arabia and ahead only of Yemen. This jarring gender gap is also evident in national data. Women account for 52 percent of Pakistan's population, yet only three percent of them work in the formal sector, according to the Federal Bureau of Statistics. One important reason for women's absence in economic activities has been the lack of women's business organizations. This smart lesson shares what we at the Center for International Private Enterprise (CIPE) learned from our work to promote women's participation in business associations and the creation of women's chambers of commerce in Pakistan.